Fiscal burden and feasibility of minimum price support: A Scenario study - Arun Reddy Anugu; A Amarender Reddy (Studies in Economy and Public Policy, 2026)
Purpose: India’s MSP–procurement–PDS system, although framed as farmer support, functions largely as a consumer subsidy. With rice and wheat sold cheaply through the PDS and global prices close to the MSP, procurement mainly ensures price assurance. Expanding assured procurement to all MSP crops raises serious concerns regarding fiscal sustainability, administrative feasibility, and market distortions. This study evaluated the fiscal implications of alternative MSP reform pathways. Methodology: Using 2024–2025 production, MSP, and wholesale price data, five scenarios were modelled: full procurement of all 23 MSP crops (upper bound); current-style procurement of 40% of paddy and wheat and 20% of others (baseline); baseline plus PDP at 10% of MSP for 20% of other crop output (partial PDP); baseline plus PDP at 20% of MSP for 40% of other output (enhanced PDP); and continued cereal procurement with universal PDP for other crops. Results: Partial procurement results in payouts of approximately ?3.7 lakh crore (USD 40.3 billion) (1.12% of GDP) while concealing large storage and inventory risks. Hybrid models provide comparable income support with lower logistical burden. Universal PDP moderately increases outlays but expands coverage and avoids procurement inefficiencies. Even a broadened PDP system would cost approximately ?1.14 lakh crore (USD 12.4 billion). Conclusions: Effective farmer price assurance does not require expanded procurement efforts. A gradual transition toward hybrid and PDP-based support can protect incomes, reduce inefficiencies, and clearly separate consumer subsidies from farmer income policy, offering a practical reform pathway for India and similar economies. Limitations: This study uses a static, single-year framework and does not capture dynamic distributional factors. Contributions: This study provides a fiscal comparison of MSP implementation pathways, introduces a hybrid procurement–PDP framework, and offers new evidence on extending income support to neglected crops and regions while minimizing fiscal expenditure.